Macrophage-Assisted Dissolution of Gold Nanoparticles - Carlander, Ulrika; Midander, Klara; Hedberg, Yolanda S; Johanson, Gunnar; Bottai, Matteo; Karlsson, Hanna L (ACS applied bio materials, 2019)
Gold nanoparticles (AuNPs) are readily functionalized and considered biocompatible making them useful in a wide range of applications. Upon human exposure, AuNPs will to a high extent reside in macrophages, cells that are designed to digest foreign materials. To better understand the fate of AuNPs in the human body, their possible dissolution needs to be explored. In this study, we tested the hypothesis that macrophages, and especially stimulated macrophages, can impact the dissolution of AuNPs in a size-dependent manner. We developed an in vitro method to compare the dissolution of citrate coated 5 and 50 nm-sized AuNPs, in terms of released gold ions as measured by inductive coupled mass spectrometry (ICP-MS), in (i) cell medium (alone) (ii) in medium with macrophages present and (iii) in medium with lipopolysaccharide (LPS) triggered macrophages (simulating inflammatory conditions). We found an evident, time-dependent dissolution of AuNPs in cell medium, corresponding to 3% and 0.6% of the added amounts of 5 and 50 nm AuNPs, respectively, after 1 week (168 h) of incubation. The dissolution of 5 nm AuNPs was further increased to 4% in the presence of macrophages and, most strikingly, 14% was dissolved in case of LPS-triggering. In contrast, only a minor increase was observed for 50 nm AuNPs after 1 week in the presence of LPS-triggered macrophages compared to medium alone. Dissolution experiments in the absence of cells highlighted the importance of biomolecules. Our findings thus show dissolution of citrate coated AuNPs that is dependent on size, presence of macrophages, and their inflammatory state. These findings have implications for understanding the transformation/dissolution and fate of AuNPs.